IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE AND TAHSIN AL-QUR’AN GUIDANCE IN THE DEVELOPMENT OF ELEMENTARY SCHOOL TEACHERS’ COMPETENCIES - Robiahasna Ritonga; Herawati; Khaerani Harahap; Zainal Efendi Hasibuan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Digital transformation through Artificial Intelligence (AI) offers significant potential for enhancing elementary school teacher competence, yet its implementation remains largely technical and fragmented when detached from teachers’ religious and personal dimensions. This study addresses this gap by examining the integration of AI-assisted learning and Qur’anic tahsin development as a holistic model of teacher competency enhancement. Employing a qualitative case study design, the research was conducted at SD Negeri 200206 Padangsidimpuan, involving elementary school teachers, Islamic Religious Education teachers, school leadership, and facilitators of AI and tahsin training programs. Data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using an interactive analytical model with methodological triangulation. The findings reveal that the use of AI tools—such as ChatGPT, Gamma, and Canva AI—significantly improves instructional effectiveness and strengthens teachers’ pedagogical and professional competencies. Furthermore, AI-integrated Qur’anic tahsin training, particularly in makhārij al-ḥurūf and tajwīd, enhances teachers’ Qur’anic recitation quality while reinforcing their religious and personal competencies. This study contributes a value-based, integrative framework for teacher professional development that bridges digital innovation and Islamic educational values. Despite its potential, the model faces challenges related to digital literacy disparities, infrastructural readiness, and the need for sustained mentoring. The study advances scholarly discourse on ethically grounded AI integration in elementary education.